PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK, KUALITAS PELAYANAN PAJAK DAN SANKSI PAJAK TERHADAP KEPATUHAN WAJIB PAJAK DAERAH LAIN KABUPATEN PONOROGO - Wibowo, Arie; Rispantyo, Rispantyo; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
Associated with the function of the local tax, the local government of Ponorogo need to better exploit the resources of local taxes to increase tax compliance in Ponorogo in paying local taxes. Tax compliance in paying taxes can be determined by factors such tax knowledge to yourself taxpayer, the taxpayer awareness, the quality of tax service, as well as the penalties for taxpayers who commits an offense. This research aims to provide empirical evidence of the influence of tax knowledge, taxpayer awareness, quality of taxation services and tax sanctions simultaneously to the taxpayer compliance in paying other local taxes in Ponorogo Regency. The population of this research is all taxpayers with a sample of 148 taxpayers. The sampling procedure used in this study is purposive sampling. Data collection techniques use questionnaires that have passed the validity and reliability tests. Test the regression requirements using the classic assumption test. Data analysis techniques use multiple linear regression analyses with absolute difference tests and hypothesis testing conducted through Test T and Test F. The results of this study show that: 1) Tax knowledge positively affects the taxpayer's tax compliance in paying other local taxes in Ponorogo Regency. 2) Taxpayer awareness positively affects the taxpayer's tax compliance in paying other local taxes in Ponorogo Regency. 3) Tax service quality positively affects the taxpayer's tax compliance in paying other local taxes in Ponorogo Regency. 4) Tax sanctions positively affects the taxpayer's tax compliance in paying other local taxes in Ponorogo Regency. 5) Tax knowledge, taxpayer awareness, quality of taxation services and tax sanctions simultaneously influences to the taxpayer compliance in paying other local taxes in Ponorogo Regency.